1996
DOI: 10.1021/np960155d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Aryltetralin Lignans in Plant Parts and among Different Populations of Podophyllum peltatum by Reversed-Phase High-Performance Liquid Chromatography

Abstract: A simple procedure for the extraction of aryltetralin lignans from Podophyllum peltatum with addition of an internal standard (acetylpodophyllotoxin) was developed. Plant material was separated into rhizomes and roots, petioles, and blades, and the lignan content of the ground tissue of these different parts was analyzed by reversed-phase HPLC. Podophyllotoxin and seven of its congeners were quantified. It was observed that the lignan content of the different plant parts may differ by orders of magnitude. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…CE quantification experiments of different Podophyllure peltatum samples showed similar results compared to those obtained by HPLC [7] ( Table I). The peaks were assigned by their UV-spectra, was well as by spiking the samples with the pure compounds.…”
Section: Figuresupporting
confidence: 73%
See 1 more Smart Citation
“…CE quantification experiments of different Podophyllure peltatum samples showed similar results compared to those obtained by HPLC [7] ( Table I). The peaks were assigned by their UV-spectra, was well as by spiking the samples with the pure compounds.…”
Section: Figuresupporting
confidence: 73%
“…Analytical methods described in literature are based on TLC and HPLC [5][6][7]. In one report [8] the root extract of P. emodi has been analyzed by means of CE.…”
Section: Introductionmentioning
confidence: 99%
“…The rhizome contains podophyllotoxin (PTOX) possessing anti-cancer properties (Jackson et al 1984a;Bastos et al 1996;Moraes et al 2002). The semi-synthetic derivatives of this compound like etoposide, etophos, and teniposide are used clinically as chemotherapeutic agents for a variety of tumors, including small cell lung carcinoma, testicular cancer, and malignant lymphoma (Stähelin and von Wartburg 1991;Damayanthi and Lown 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Podophyllotoxin production is not restricted to the roots as low amounts of podophyllotoxin (0.003-0.229% d.w.) are also found in P. hexandrum leaves (Pandey et al 2013). Furthermore, several researchers reported podophyllotoxin production in the leaves of P. peltatum (Bastos et al 1996;Moraes et al 2000Moraes et al , 2002Cushman et al 2006;Zheljazkov et al 2011). The most recent population study was by Zheljazkov and coworkers who found up to 2.53% (d.w.) podophyllotoxin (Zheljazkov et al 2011).…”
Section: Introductionmentioning
confidence: 99%